Investigating the Tribocorrosion Behaviour of NiTiNOL60 Alloy in Engineering and Biomedical Applications - An Overview - Okoani, Anthony O; Nand, Ashveen; Jiang, Cho-Pei; Ramezani, Maziar (MDPI AG, 2024)
This review covers the literature that is currently accessible, as well as emerging research into the performance of NiTi-based alloys exposed to corrosive environments in both engineering and medical applications. It provides an overview of the state-of-the-art research in the study of tribocorrosion of Ni-rich NiTi alloy by highlighting significant discoveries, research approaches, and future research directions following the limited reviews on tribocorrosion in the past decade. The practical impacts, as well as the economic implications of tribological applications on daily life, coupled with the increasing failures of metals and biomaterials, make it imperative to investigate tribocorrosion and update the subject area on the recent focus. Tribocorrosion is commonly observed on the surface of different metals, including NiTi alloys, such as NiTiNOL60 (60 wt.% Ni and 40 wt.% Ti), which possess unique properties applicable across various engineering and biomedical fields. In its application, the material experiences wear due to the depassivation of tribofilms caused by relative motion (sliding, fretting, or impact) in aggressive environments, including corrosive mediums, high temperatures, and pressures. This study elucidates the synergistic interactions between mechanical wear, corrosion, and their associated tribocorrosion mechanisms in corrosive media.
Keywords: 40 Engineering; 4003 Biomedical Engineering; 0914 Resources Engineering and Extractive Metallurgy; 4016 Materials engineering; 4019 Resources engineering and extractive metallurgy